Tiempo Muerto - Hau, Caroline (Quezon City : Bughaw, 2019)
"Two women meet on the island where they shared a childhood. One is looking for her mother, the other her yaya. One is an Overseas Filipino Worker, the other an heiress. In an old bahay na bato haunted by scandal and tragedy, secrets and ghosts, the women find their lives entangled and face the challenge of refusing their predetermined fates and embracing their open futures."
English
Keywords: Philippine fiction (English).